2020
DOI: 10.1038/s41370-020-0250-2
|View full text |Cite
|
Sign up to set email alerts
|

User-centered design of an air quality feedback technology to promote adoption of clean cookstoves

Abstract: Background Recent work has examined behavioral reactivity associated with personal awareness of electronic sensors monitoring the use of environmental health products, including cookstoves. These studies suggest that sensors could be used as behavior change tools. Objective We present a human-centered design approach toward the development of a household air quality feedback technology intended to improve consistent and exclusive use of liquid petroleum gas (LPG) stoves provided as part of a health efficacy st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 35 publications
1
14
0
2
Order By: Relevance
“…Findings from this study provide important insights for the last of these domains. In accordance with qualitative literature in other LMICs [23,44,45,54,69], we found that whilst the majority of participants reported LPG for cooking was clean (95%) and cooked food quickly (88%), they also perceived it to be both unsafe (64%) and expensive (69%). Familiarity with the fuel lessened these negative perceptions, with households reporting exclusive use of LPG being more likely to express positive views about it (more so than mixed and non-LPG users).…”
Section: Fuel Use Patterns and Their Determinantssupporting
confidence: 88%
See 4 more Smart Citations
“…Findings from this study provide important insights for the last of these domains. In accordance with qualitative literature in other LMICs [23,44,45,54,69], we found that whilst the majority of participants reported LPG for cooking was clean (95%) and cooked food quickly (88%), they also perceived it to be both unsafe (64%) and expensive (69%). Familiarity with the fuel lessened these negative perceptions, with households reporting exclusive use of LPG being more likely to express positive views about it (more so than mixed and non-LPG users).…”
Section: Fuel Use Patterns and Their Determinantssupporting
confidence: 88%
“…Of those households reporting use of LPG for cooking (as either a primary or secondary cooking fuel), four-fifths (81%) used it alongside a polluting solid fuel (wood or charcoal). It is well established that this “fuel stacking” is the norm for many households across SSA, Asia and Latin America [ 34 , 35 , 51 , 52 , 53 , 54 ]. The benefits of clean cooking with LPG are clearly reduced with a greater amount of fuel stacking with solid fuels and kerosene.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations